Energy Efficient Secure Routing in Manets Based on Multipath Erasure Coding (International Journal of Engineering and Computer Science, 2015)
Wireless networks can be mainly categorized as, infrastructure wireless networks and infrastructure-less wireless networks. MANET is a type of infrastructure-less wireless network. It is a collection of nodes that dynamically connected together to form a network without using any fixed infrastructure. As it is infrastructure less network, the information or data packets are send between the nodes with the help of radio signals and each node act as routers. Providing efficient networking services in MANETs is very challenging due to mobility and unpredictable radio channel: a significant number of packets can be corrupted or lost. To increase reliability, various measures have been proposed. A more efficient way is to use Network Coding on top of path redundancy and send different, encoded packets on each path. Network coding can improve throughput efficiency. In this work proposing Multipath Erasure Coding for high energy efficient. The use of erasure codes in networks has proved to be promising in order to make communication more robust against both independent and correlated data losses. In particular, erasure codes are an appealing solution to provide communications with increased reliability. Experimental results exhibit consistency with the theoretical analysis, and show that the proposed method achieves higher efficiency when compared to other routing protocol.